2005
DOI: 10.1111/j.1440-1827.2005.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased norepinephrine‐associated adrenomedullary inclusions in Parkinson's disease

Abstract: The association with Parkinson's disease (PD) of adrenomedullary inclusions, known as 'hyaline globules' or 'adrenal bodies', has been reported for over 35 years. However, the common perception has been that adrenomedullary chromaffin cells cannot be recognized as pathological cells in PD. In the present study, we discovered that the number of adrenomedullary inclusions per unit area of the adrenal medulla was larger in PD and other Lewy body disorders (LBD) than in other neurological diseases and controls wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The adrenal gland is evolutionarily related to the sympathetic ganglia, and its capsula contains autonomic nerves and ganglia. There is evidence of involvement of the peripheral ANS in the adrenal gland in PD 89–91. One group reported adrenomedullary inclusions (adrenal bodies) in some patients, which they recognized to be Lewy‐body‐related (though they were also associated with other neurological diseases) 92.…”
Section: Adrenal Glandmentioning
confidence: 99%
“…The adrenal gland is evolutionarily related to the sympathetic ganglia, and its capsula contains autonomic nerves and ganglia. There is evidence of involvement of the peripheral ANS in the adrenal gland in PD 89–91. One group reported adrenomedullary inclusions (adrenal bodies) in some patients, which they recognized to be Lewy‐body‐related (though they were also associated with other neurological diseases) 92.…”
Section: Adrenal Glandmentioning
confidence: 99%
“…There is evidence of involvement of the peripheral ANS in the adrenal gland in PD. [89][90][91] One group reported adrenomedullary inclusions (adrenal bodies) in some patients, which they recognized to be Lewy-body-related (though they were also associated with other neurological diseases). 92 Lewy-body-related a-synucleinopathy was also detected in the sympathetic ganglia cells and nerve fascicles in the adrenal gland in 11% of 783 general autopsy cases.…”
Section: Adrenal Glandmentioning
confidence: 99%
“…The sympathetic nervous system has already been recognised as a pathological site in PD [44]. PD is frequently accompanied by a variety of autonomic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the number of adrenomedullary inclusions per unit area of the adrenal medulla in patients complaining of PD and other Lewy body disorders (LBD) was higher compared to other neurological diseases and apparently healthy subjects without any autonomic dysfunctions, and correlated with the duration of LBD. It was reported that the cells which contain adrenomedullary inclusions are all norepinephrine-secreting chromaffin cells [44]. The presence of adrenomedullary inclusions indicates cellular degeneration which may be ascribed to a defect of norepinephrine reuptake and metabolism [47] or due to a long-term acceleration of the secretion of adrenomedullary norepinephrine in PD resulting in high circulating levels of norepinephrine [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation